Korelasi Antropometri dan Kecemasan terhadap Kecepatan Lari 200 Meter pada Atlet Club Pandanaran Atletik Center Semarang - Andhika Putra Tama; Sungkowo Sungkowo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the relationship between anthropometric factors and anxiety on the 200-meter sprint speed of athletes at the Pandanaran Athletics Center in Semarang. The background of this study is based on the importance of combining physical and psychological aspects in determining the optimal performance of short-distance runners. The method used is a quantitative approach with a correlational design. The study subjects consisted of 36 athletes selected through purposive sampling. Anthropometric variables included height, weight, and leg length; anxiety was measured using the CSAI-2 questionnaire. Running speed data was obtained through timing of the 200-meter run. Regression analysis results showed that, simultaneously, height, weight, and anxiety significantly influenced running speed (sig. = 0.006 < 0.05). Partially, only weight and anxiety had significant effects, with a negative coefficient for weight and a positive coefficient for anxiety. Meanwhile, height and leg length do not have a significant effect. The coefficient of determination (R²) value of 36.3% indicates that the independent variables can explain part of the variability in running performance. These findings emphasize the importance of training that integrates physical and psychological dimensions.